Terms of Trade Disturbances, Real Exchange Rates, and Welfare The Role of Capital Controls and Labor Market Distortions (IMF Working Papers, 1989)
Many arguments that have been advanced in favor of maintaining capital controls within the EC have not paid sufficient attention to the welfare consequences of this type of market intervention. Our paper provides a simple, optimizing framework in which the welfare consequences of capital controls can be assessed. Two main issues are considered. First, how do capital controls affect the adjustment of macroeconomic variables to real disturbances? Second, what is the nature of second best arguments for maintaining capital controls given that certain distortions will remain after the European single market is in place in 1992?